ANALISIS GAYA BELAJAR PADA SISWA KELAS 7 DAN IMPLIKASI KECENDERUNGAN PERILAKU BELAJAR DI SMPN 17 MEDAN - Melati Putri Agnesia Lubis; Katerina Br Barus; Rifki Ramadhan Sari Sipahutar; Setyo Rini Winarsih (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the learning styles of seventh-grade students and the implications of learning behavior tendencies at SMP Negeri 17 Medan. This research used a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research subjects consisted of four seventh-grade students, namely Intan Dewi, Nazril Badrin Nasution, Aisah Nuraini, and Berlian Akila Zidni Lubis. Data analysis was carried out through the stages of data reduction, data presentation, and conclusion drawing. The results showed that students have diverse learning style tendencies and do not only focus on one particular learning style, but rather use a combination of visual, auditory, and kinesthetic learning styles in the learning process. These differences in learning styles influence students’ learning behavior, such as the way they understand material, concentration levels, activeness in learning, learning motivation, and social interaction in the classroom. In addition, the learning environment, classroom atmosphere, and teachers’ teaching methods also affect students’ comfort and focus during learning activities. The findings indicate that varied, flexible, and student-centered learning methods can help improve student engagement and learning effectiveness in schools.